Analysis of Factors Influencing the Young Generation in Choosing Tourism Majors at LPK OTC Bali Gianyar - I Wayan Erik Susanto; Nengah Nita Loktika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The recovering global tourism sector post-pandemic demands the provision of competent, fast, and adaptive Human Resources. Job Training Centers (LPK) play a vital role in providing fast-track vocational education focused on practical skills to meet this demand. This study aims to analyse the internal, external, and institutional factors influencing the decision of the Younger Generation to choose a tourism major at LPK OTC Bali Gianyar. Utilizing a quantitative approach with a descriptive-associative design, primary data were collected through structured questionnaires using a Likert Scale. The sampling technique employed was Proportional Random Sampling or Saturated Sampling. Data analysis methods involved Descriptive Analysis, Classical Assumption Tests, and Multiple Linear Regression Analysis. The results of the validity test (>0.3) and reliability test (>0.7) indicated that the research instrument was reliable and consistent. Regression analysis results showed that simultaneously (F-test < 0.05), internal, external, and institutional factors significantly influenced the major selection decision. Partially (t-test), external factors exerted the most dominant influence, followed by internal and institutional factors. Career prospects and family support were the two most significant partial variables driving student motivation. These findings reinforce the Theory of Planned Behaviour and Holland's Theory regarding personality and work environment congruence. Practically, this study suggests that LPK OTC Bali Gianyar strengthen its digital promotion strategies, expand global industry partnerships for internship programs, and provide structured career guidance